Analogues of (3R)-7-Hydroxy-N-[(1S)-1-{[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl)-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide (JDTic). Synthesis and In Vitro and In Vivo Opioid Receptor Antagonist Activity - Runyon, Scott P. (2010)
The synthesis of compounds 6, 7a,b, 8a,b, 9a,b, and 10a,b where the amino -NH- group of JDTic (3) was replaced with an aromatic =CH–, CH(2), O, S, or SO group was accomplished and used to further characterize the SAR of the compound 3 class of κ opioid receptor antagonists. All of the compounds showed subnanomolar to low nanomolar K(e) values at the κ opioid receptor. The most potent compound was 7a, where the amino -NH- group of 3 was replaced by a methylene (-CH(2)-) group. This compound had a K(e) = 0.18 nM and was 37- and 248-fold selective for the κ relative to the μ and δ opioid receptors, respectively. Similar to compound 3, compound 7a antagonized selective κ agonist U50,488-induced diuresis after s.c. administration in rats. In contrast to 3, where κ antagonist activity lasted for three weeks, compound 7a did not show any κ antagonist activity after one week.